Hemicellulose fiber gum from distillers grain: isolation, structure and properties - E, Xinyi (Kansas State University, 2010)
Isolation of hemicellulose from distillers dry grain with solubles (DDGS) was investigated. Hemicellulose fiber gum (HFG) is a mixture of hemicelluose, protein, ash and starch. It was extracted from a commercial DDGS by heating with or without alkali. Three extraction methods (water heating, alkaline heating and alkaline hydrogen peroxide heating) were evaluated. Yield of HFG and the recovery of hemicellulose were obtained. High heating temperature (100 and 120°C), alkali or hydrogen peroxide facilitated the release of hemicellulose from the cell wall matrix. However combining alkali with 2.5% H2O2 did not extract more hemicellulose out than did alkali alone. The highest hemicellulose recovery was 32% achieved by cooking at 120°C with 2% alkaline solution. Hemicellulose can function as an emulsifier in the oil-in-water emulsions, such as beverage, and potentially replace gum arabic. HFGs obtained by a series of extracting methods were applied in both the concentrated emulsion with the gum: oil: water ratio of 0.5:1: 8.5 and the diluted emulsion with the gum: oil: water ratio of 0.005: 0.01: 1. The emulsion stability was evaluated by turbidity and creaming test. HFG extracted by 2% NaOH solution at 120°C and HFG extracted by 2% NaOH and 2.5% H2O2 solution at 100°C showed the best emulsifying ability among 15 HFG samples. DDGS was produced from corn, sorghum, wheat in the lab. HFGs extracted from sorghum and wheat DDGS were compared with that from corn DDGS. The composition of the three DDGS varied in protein, fat and non-starch carbohydrate contents. Sorghum and wheat DDGS contained higher levels of protein and lower levels of fat and non-starch carbohydrate than corn DDGS. HFG was extracted by 2% NaOH solution at 100°C for one hour and purified by 100% ethanol. The yield of HFG from corn, sorghum and wheat DDGS was 21.08, 11.07, 11.64% respectively, while the hemicellulose recovery was 30.95, 29.74, 22.71% respectively. The water extractable hemicelluloses from all three DDGS had similar ratios of arabinose to xylose.
Keywords: Hemicellulose; Distillers Grain; Agriculture, Food Science and Technology (0359)